Tata Bahasa Kasus dalam film Kena: Bridge of Spirit Berdasarkan Perspektif Charles J. Fillmore - Nuratul Muntahana; Abdul Muntaqim Al Anshory (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to identify the modality and proposition in the movie "Kena: Bridge of Spirit" using Charles J. Fillmore's case grammar theory. This type of research is descriptive qualitative research. The object of this research is the movie "Kena: Bridge of Spirit" directed by Hunter Schmidt. The data collection techniques used are listening and note-taking methods. Data analysis in this study went through three stages: data reduction, data presentation, and conclusion drawing. The data validation techniques used are to increase persistence and triangulation. The results of the research on the movie "Kena: Bridge of Spirit" based on Fillmore's case grammar theory consists of four modalities (tense, negation, mode, and aspect) and ten propositions (agent, experience, place, instrument, time, objective, purpose, accompaniment, source, and benefactive).